Estimating harmonic impact of individual loads using harmonic phasor data. (13th July 2017) - Wang, Yang; Xu, Wilsun; Yong, Jing; Chen, Kun‐Long
Summary: Owing to increased capabilities of power quality monitors, synchronized harmonic phasor data are becoming more widely available. Taking advantage of the new data, this paper presents a new and effective method to solve the problem of how to estimate the harmonic impact of several individual loads on the harmonic voltages at a specific location of a power network. The method uses the independent fluctuation of the harmonic sources and is solved as a blind source separation problem. The proposed method has been verified through simulation verification where harmonic currents measured at actual substations are used as input so realistic load fluctuations are considered. Furthermore, lab experiments are conducted to validate the proposed method.